Reversibility of tachycardia-induced cardiomyopathy after radiofrequency ablation of incessant supraventricular tachycardia in infants. Issue 3 (September 1995) - Sanchez, C.; Benito, F.; Moreno, F.
Abstract : Tachycardia-induced cardiomyopathy developed in a 3 month old infant with permanent junctional reciprocating tachycardia, which was incessant despite medical treatment. The patient underwent transcatheter radiofrequency ablation. There were no complications and 8 months after the procedure the patient was symptom free without medication.